Towards Tax Administration 3.0: Bracing the Challenges in Mobile Application Development - Sidiq, Darmawan; Raharjo, Teguh; Trisnawaty, Ni Wayan (SAFE-Network, 2024)
Tax Administration 3.0 calls for tax administrations to be a high-tech adaptive organization with human touch. To that extent, tax administrations worldwide have developed mobile app as a taxpayer touchpoint. As the results of tax administrations’ digital maturity assessment shows major room for improvement, the mobile app development also faced with challenges. This study aims to investigate challenges in tax services mobile app development using M-Pajak as a case study. The descriptive qualitative approach used as our research method is composed of literature review, semi structured interview, open coding, and thematic analysis. Our study finds that M-Pajak development faces challenges related with project management and application requirements. To mitigate the challenges, it is important to ensure that projects are sufficiently staffed. Furthermore, change management must be implemented by focusing on user needs, who largely determine the application success. Meanwhile, fragmentation can be considered as the most critical challenge as it affects other challenges. Diversity of platforms and devices in which the mobile application will be operated potentially affects other factors, such as interoperability, user experience, privacy, and security. This study is important for tax administrations to anticipate challenges in developing their mobile app. Finally, this study also enriches the literature through the investigation of the mobile app development challenges in the context of tax services mobile app.